Determinants of environmental reporting quality in Malaysia - Sulaiman, Maliah; Abdullah, Norhayati; Fatima, Abdul Hamid (International Islamic University Malaysia, 2014)
The study examines the relationship between share ownership distribution, profitability, firm size and leverage with the quality of environmental disclosure in annual reports in 2009, two years after Malaysia made corporate social responsibility disclosure mandatory for all listed companies. Three theories; legitimacy, resource based view and information provided the theoretical underpinnings of the study. A content analysis of the annual report of 164 companies in the environmentally sensitive industries (ESI) was undertaken. Disclosure quality was measured using a self-developed index adapted from prior studies. The findings revealed a significant positive association between firm size and leverage with the quality of environmental reporting, thus providing the support for legitimacy theory. Given that share ownership distribution and profitability had no significant relationship with the quality of environmental reporting, the use of resource based view and information cost theories did not provide any support in explaining environmental reporting behavior of companies in the environmentally sensitive industries in Malaysia.